FACTORS OF SPREADING THE NOSOCOMIAL URINARY TRACT INFECTION - KH.KH. RIZOEV; D.A. RAKHIMOV; M.S. TALABZODA (Avicenna Tajik State Medical University, 2019)
Objective: Exploring the factors which contributes the spreading the nosocomial urinary tract infection (NUTI). Methods: Random sampling method analyzed 248 medical cards of patients with benign prostatic hyperplasia for 2016-2018. 154 of them were underwent open adenomectomy, and 94 - transurethral resection of the prostate (TURP). The prevalence of NUTI was studied depending on the patient's age, duration of surgery, duration preoperative period and duration of bladder catheterization. Results: In 31 cases, the NUTI was identified, which amounted to 12.5%. After the open adenomectomy, the NUTI had 21 observations (13.6%), and after the TURP - in 10 cases (10.6%). The most typical manifestations of NUTI were: urethritis - 32.2%, postoperative wound suppuration - 25.8%, cystitis - 19.3%. It has been found that the frequency of development of NUTI is influenced by the duration of the preoperative period. Thus, among patients who had no more than 2 days of preoperative surgery, the NUTI was 5 times less common than patients with a longer preoperative period, with a frequency of 5.0% and 26.1%, respectively (р<0.001). Statistically significant differences in the frequency of NUTI was found, depending on the duration of catheterization of the bladder: at the terms of catheterization up to 6 days and more than 6 days frequency of NUTI was 6.5% and 22.6% respectively (р<0.001). Conclusion: The most frequent clinical manifestations of NUTI were the suppuration of postoperative wound and urethritis. The main factors influencing the spread of NUTI are the duration of the preoperative period and the duration of bladder catheterization.